PENGARUH CITRA MEREK DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN NASABAH MEMILIH TABUNGAN BANK SYARIAH MANDIRI - BAGUS I, ADITYA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:Indonesia is a country with a majority of the population is moslem. That conditions in our society is showing a trends change, where previously the conventional banking system tends to be preferred, and become switch using sharia-based banking system. People tends to use brand image as a direction to evaluate a product. On the other hand the bank will implement a marketing strategy aimed to influencing public, one through sales promotions. This research aims to discuss and analyze the influence of brand image and sales promotions on customers choosing decisions of Bank Syariah Mandiri’s saving. The sample in this research is customer who get sales promotion services for a savings product categories amount to 200 respondent with accidental sampling technique. Data collected with questionnaire, while technique analyse data used multiple regression analysis. Based on the test result known that brand image and sales promotion has significant influence to purchase decision. Keywords: brand image, sales promotion, purchase decision.